2001
DOI: 10.1149/1.1371799
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a Nickel-Hydrogen Cell: Phase Reactions in the Nickel Active Material

Abstract: A nonisothermal model of a nickel-hydrogen cell has been developed with the consideration of multiple phases in the nickel active material. Important mechanisms inside a nickel-hydrogen cell, such as mass balances of active species, kinetics of electrochemical reactions, and the energy balance of the whole cell, etc., have been included in the model. The model predictions under different conditions are presented and analyzed. These predictions showed that nickel phase reactions have significant influences on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…and water is reduced to hydrogen atoms at the MH Mathematical models have been developed for both Ni electrode, which can subsequently be absorbed in the and MH electrodes [6,7], and for NiMH [8,9]. Unforhydride-forming intermetallic compound [1], according to tunately, these battery models do not predict the interactive 2 2 behaviour of the battery voltage, temperature and internal…”
Section: Introductionmentioning
confidence: 99%
“…and water is reduced to hydrogen atoms at the MH Mathematical models have been developed for both Ni electrode, which can subsequently be absorbed in the and MH electrodes [6,7], and for NiMH [8,9]. Unforhydride-forming intermetallic compound [1], according to tunately, these battery models do not predict the interactive 2 2 behaviour of the battery voltage, temperature and internal…”
Section: Introductionmentioning
confidence: 99%
“…The battery cell voltage profiles in a cycle of charge, overcharge, self-discharge, and discharge are shown in Fig. 4 and compared against the TRW 30 Ah module data [23]. As can be seen, the model fits the experimental data very well for the normal charging (first 10 h) at all three temperatures.…”
Section: B Battery Systemmentioning
confidence: 81%
“…The significant discrepancy between the model and the data is seen when discharging below 1.15 V, where the experimental data show larger discharge capacity, and the temperature effect is more pronounced. This may be due to the fact that the appearance of°-phase of nickel oxyhydroxide contributes to the discharge capacity [23]. Although the model does not account for the discharge behavior below 1.15 V, it can be concluded that the model matches the experimental data very well within the normal operation range.…”
Section: B Battery Systemmentioning
confidence: 88%
See 1 more Smart Citation
“…where R is the universal gas constant (R = 8.314472), F is the Faraday constant (F = 96485.3415), T is the temperature of the battery module, which was maintained at about 298.15 K by a thermostatic chamber, C is the battery capacity, v Nieq is the standard potential of the nickel electrode (v Nieq = 0.427 V [9]), and v MHeq is the standard potential of the metal hydroxide electrode (v MHeq = 0.9263 V [10]). …”
Section: Voltage Hysteresis and Relaxation Of Nimh Batterymentioning
confidence: 99%